ANALISIS PENGARUH FIRM SIZE, BOOK TO MARKET RATIO, PRICE EARNING RATIO, DAN MOMENTUM TERHADAP RETURN PORTOFOLIO SAHAM - Darusman, Dery; Prasetiono, Prasetiono (Diponegoro Journal of Management, 2012)
This research aims at studying the fundamental variables that can be used as predictors short return on investment. Object of research used in this study is the company incorporated in LQ 45 during the 2009-2011 study periode. The variables studied are Firm Size, Book to Market Ratio, Price Earning Ratio and Momentum. Analytical techniques used in this study is the multiple linear regression. This research was conducted with quantitative methods to the financial statements of listed companies in LQ 45 during the period 2009-2011. The total study sample was 27 companies that are consistently listed in 7 (seven) in the period of observation in LQ 45 index and 27 companies are determined through purposive sampling method. Method of hypothesis testing using different test t-test and multiple linear regression. The results showed Firm Size has no significant positive effect on portfolio stock returns. Book to Market Ratio has no significant positive effect on portfolio stock returns. Price Earning Ratio has no significant negative impact on the company's portfolio stock return. Momentum occurred at week 2, 4, and 8 after the formation of stock prices. This could indicate that investors tend to speculative trading in shares on the Indonesia Stock Exchange.